Children Beyond Childhood in a Rural Community of India (Indian Journal of Social Science and Literature (IJSSL), 2025)
Child labour is a significant issue in rural India, where lack of education, social norms, and poverty push children into premature work, depriving them of their rights and opportunities. For many young people, adolescence is marked not by opportunity but by challenges such as poverty, limited access to education, and the burden of premature responsibilities. Although for many children, the transition from infancy to adolescence is often shadowed by financial difficulties and early responsibility, it should be a period of learning, growth, and opportunity. While numerous provisions of the law and international treaties protect children's rights, millions of children still work in dangerous jobs that take away their fundamental rights to education, health care, and a good upbringing. This study examines the impact of child labour on the physical, mental, and educational well-being of children, using Bagru, Rajasthan, as a case study. Findings highlight safe working conditions, limited access to education, and poor healthcare. Effective policy interventions, improved educational infrastructure, and community support are essential to breaking this cycle and ensuring children's rights are upheld. At the same time, awareness projects should be established in conjunction with community-driven initiatives to create a lasting impact. A multi-pronged approach is necessary to protect children and secure their future.